Discourse functions of grammatical subject in results and discussion sections of research article across four disciplines - Ebrahimi, Seyed Foad; Chan, Swee Heng; Abdullah, Ain Nadzimah (University of Antwerp, 2014)
This research analyzes the discourse functions of grammatical subjects used in results and discussion sections of research articles across four disciplines. To this end, sixteen results and discussion sections from four disciplines, namely, English Language Teaching, Economics, Biology and Civil Engineering (four from each discipline), were analyzed using the categorizations of discourse functions of grammatical subjects established by Gosden (1993). There were marked disciplinary differences in terms of the discourse functions served through the application of the grammatical subjects in the four sets of the results and discussion sections. These disciplinary differences were clearly shown in all the four domains of the discourse functions of the grammatical subject along with their subcategories. This result suggests that the discourse functions of the grammatical subject are strongly related to the public aims, norms and conventions of specific disciplines as well in the contexts in which it is realized.